Persepsi Guru PAI terhadap Penggunaan Video Animasi untuk Memahami Nilai Tanggung Jawab pada Mata Pelajaran PAI - Mirda, Laila Rahma; Waqfin, Mohammad Saat Ibnu; Wahyudi, Wahyudi (Lembaga Yasin AlSys, 2025)
This study aims to determine the perception of Islamic Religious Education teachers towards the use of animated videos in facilitating the understanding of the values ​​of responsibility in Islamic Religious Education subjects at MTs Darussalam Ngoro Jombang. Descriptive qualitative method with data collection techniques through interviews and non-participant observation, where researchers are not directly involved in the activities observed. The research sample consisted of the principal and four Islamic Religious Education teachers. The subjects of this study were Islamic Religious Education teachers. In addition, this study also aims to determine the perception of Islamic Religious Education teachers towards the use of animated videos in facilitating and to determine the supporting and inhibiting factors faced by Islamic Religious Education teachers in using animated videos as a medium to teach the values ​​of responsibility in Islamic Religious Education subjects. The results of the study indicate that animated videos are considered an effective medium in facilitating students' understanding of the values ​​of responsibility. The main supporting factors are the visual appeal and storyline presented by animated videos, which increase student motivation and involvement in learning. However, limited access to technology and teacher skills in operating devices are significant inhibiting factors.